Legal Protection for Creditors Due to Cancellation of Deed of Granting Mortgage Rights (Apht) and Power of Attorney to Charge Mortgage Rights (Skmht) - Selinda, Risma; Arpangi, Arpangi (Jurnal Konstatering, 2025)
Abstract. The agreement between the bank and the customer will create a relationship involving debts. In banking practice, the bank must ensure that the funds lent protected by legal collateral. Therefore, the role of the Land Deed Official (PPAT) is important to ensure that the mortgage binding process. This is an effort to provide legal protection for creditors. The purpose of this study is to analyze: 1) Legal protection for creditors due to the cancellation of APHT and SKMHT at PT BPR BKK Purwodadi (Perseroda). 2) Judge's considerations in the decision on the lawsuit for the cancellation of APHT and SKMHT at PT BPR BKK Purwodadi (Perseroda) with case number 41/Pdt.G/2023/PN Pwd. This type of research is sociological juridical research. The approach method in this research is a Qualitative approach. The types and sources of data in this research are primary data and secondary data obtained through interviews and library studies. The analysis in this research is descriptive analysis. The results of this study are that legal protection for creditors is realized by ensuring that the credit granting process runs according to applicable provisions, through the creation of a credit agreement in the form of a notarial deed. The legal relationship with Case Number 41/Pdt.G/2023/PN Pwd is a debt-receivable relationship.Keywords: Creditors; Legal; Officers; Protection.